Ethanomedicinal uses of some important plants of Jhajjar district, Haryana, India - J. P. Yadav; Suresh Kumar (Environment Conservation Journal, 2003)
A large, number of rural people are still dependent for much of their therapeutic needs on the plants of their vicinity. The present paper incorporates the result of ethanomedicinal uses of widely use indigenous medicinal plants. Information on 30 plants along with medicinal application are given in the paper.